DEVELOPMENT OF ENERGY EFFICIENCY NODE SENSOR METHOD IN INTERNET OF THINGS (IOT) SYSTEM FOR MONITORING ENVIRONMENTAL CONDITIONS - Ryanto
Nowadays, the internet of things (IoT) technology is widely used for monitoring systems, especially for monitoring conditions of temperature, humidity, ambient, and electrical energy use of household appliances in residential areas. The concept of wireless sensor networks (WSN) is widely adopted in various IoT projects because it provides ease and flexibility in both installation and configuration. WSN consists of sensor nodes which generally have limited resource problems due to using battery energy sources. Another problem is the amount of sensing data that must be transmitted to the sink or gateway. This is due to the fact that data processing in the WSN consumes less energy compared to the data transmission process involving the use of a communication subsystem. In this study, a modified energy efficiency model was proposed by combining a data-based approach with a task-based approach to reduce a large amount of energy consumption at each sensor node to extend the life span of sensor nodes. The proposed method is by modify the data summarization technique to reduce data combined with the duty-cycle technique for resource management, also utilizing RTC internal memory as a storage of sensing data. To prove the value of efficiency and effectiveness of the method, in this study a prototype was designed to test that the proposed method was better in terms of energy consumption and the amount of data traffic compared to other similar methods. The test scenario is done by comparing the proposed method with other methods, namely continuous, summarization, and duty-cycle. The test results show that the proposed method (modified method) has an energy efficiency level of 0.25 times more efficient than the duty-cycle method, 1.3 times more efficient than the summarization method and 1.2 times more efficient than the continuous method. For data traffic, the test results show that the proposed method has a data efficiency level of 14 times more efficient than the duty-cycle method, 2 times more efficient than the summarization method and 15 times more efficient than the continuous method. Whereas for the reliability of data sent by sensor nodes using the proposed energy efficiency method it has an accuracy of 98.2%.